Secondary hypertension: beyond the diagnosis - de Azevedo, Patrícia (2025)
Introduction: Hypertension is a multifaceted condition, often attributed to several secondary causes. Understanding these causes is crucial due to the potential lethality of some conditions, although rare, that affect both the individual and their family. Case description: A 26-year-old female patient, without any significant past medical history, presented at her Family Health Unit (FHU) with a headache and high blood pressure. Following the study of secondary causes, a mass was detected in the adrenal gland, which turned out to be an adrenocortical carcinoma producing cortisol and androgens, locally advanced, and with liver metastasis. The patient was proposed for palliative chemotherapy, which she did not complete. She was monitored at the Porto Hospital Center and simultaneously with the family doctor until her death. Comment: This clinical case aims to illustrate a rare cause of secondary hypertension diagnosed in primary health care and emphasizes the importance of the family doctor in its correct identification and guidance.